The Impact of Service‐Learning Targeting Apparel Design Majors: A Qualitative Analysis of Learning Growth. (1st March 2018) - Eike, Rachel J.; Myers, Beth; Sturges, Diana
Abstract : To implement service‐learning in an apparel course, students led a mending and alterations shop that served the campus community. This study investigated the impact of participating in service‐learning on students' skills in apparel construction, management, and communication. Students completed task log reflections and midterm and end of term learning growth reflections. This qualitative information was analyzed and six discipline‐specific themes emerged. The themes were as follows: (i) apparel design skills, (ii) collaboration, (iii) self‐efficacy and growth, (iv) problem‐solving, (v) communication and terminology, and (vi) comfort zone. Overall, the service‐learning component was deemed a valuable way to prepare students for careers in the fiber, textile, and clothing industry.